New genre Arctic art in the city of Rovaniemi:Promotion of de-Arctification and pluralism - Huhmarniemi, Maria; Hiltunen, Mirja (Routledge, 2022)
The chapter examines the communally and interculturally constructed video work Possible worlds in terms of its arts-policy meanings related on whiteness, living environments and youth. The video art work consists of seven episodes relating to the living environments of young women residing in different parts of Europe. The aim is to consider what kinds of meanings these young women produce related on the places they inhabit, and how the critical perspective on whiteness could challenge the ways how the knowledge of the place has been produced in the video art work. The foundation of the chapter is arts-based research, where the artist-researcher is a participant in constructing the content of the art in collaboration with the human subjects of the study, and in which the production of the art intrinsically relates to both the research methodology and the presentation of results. The chapter draws on experiences of inhabiting a white world as a white, and explores how taking whiteness under a critical retrospective might produce new ways of understandings of living conditions produced in the video art. Keywords: art-based research; whiteness; communal art; ‘new’-materialism; young people; interculturalism; gender; social engagement; plurality Imaginaries of the Arctic cause so-called Arctification that does not resonate with experienced realities of the region as a multiethnic, multicultural and multilingual place. This chapter is based on long-term art-based action research aiming to influence contemporary art, art education, transculturalism and inclusion in the Arctic, especially in the city of Rovaniemi. The research is based on need to consider the richness and the variety of the circumpolar world and to the discussion on pluriverse, new genre public art, and new genre Arctic art. The chapter concludes that socially engaged art can promote the identification of minority cultures, encounters amongst members of different cultures and representations of multiculturalism and transculturalism in public space ...